Genetic Variability of some Palestinian Fig (Ficus Carica L.) Genotypes Based on Pomological and Morphological Descriptors - Rezq Basheer-Salimia; Murad Awad; Yamen Hamdan; Munqez Shtaya (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Characterization of fruit species is recognized as a primary and essential step towards protecting, conserving, maintaining, and conducting any future breeding program. The aim of this study is the genetic characterization of twelve fig genotypes (Ficus carica L.) from the southern region of the West Bank, Palestine, based on 41 pomological and morphological traits developed by IPGRI and CIHEAM (2003) with some minor modifications. Results showed a considerable diversity among all tested genotypes at both pomological and morphological levels. UPGMA dendrogram clustered the genotypes into four clusters (Fig. 1). The first (I) consisted of one genotype (Khdari). The second cluster (II) consisted of four genotypes (Ghzali, Bladi, Shhami and Hmari). The third cluster (III) consisted of four genotypes (Mwazi, Moozi, Ruzzi and Mouze). The fourth cluster (IV) consisted of three genotypes (Aswad, Swadi and Smari). Genetic distances ranged from 0.517 to 0.863 with a mean of 0.690. “Ruzzi and Mouze” were the most closely related genotypes, followed by “Ruzzi and Moozi”; “Moozi and Mouze”; “Mwazi and Ruzzi” and “Swadi and Smari”. In contrary, “Khdari and Aswad” and Ghzali and Aswad” were the most distantly related ones.